Isolation of Porcine Reproductive and Respiratory Syndrome Virus GP5-Specific, Neutralizing Monoclonal Antibodies From Hyperimmune Sows - Young, Jordan E.; Dvorak, Cheryl M. T.; Graham, Simon P.; Murtaugh, Michael P. (Frontiers in Immunology, 2021)
Porcine reproductive and respiratory syndrome (PRRS) is a devastating disease which impacts the pig industry worldwide. The disease is caused by PRRS viruses (PRRSV-1 and -2) which leads to abortions and other forms of reproductive failure in sows and severe respiratory disease in growing pigs. Current PRRSV vaccines provide limited protection; only providing complete protection against closely related strains. The development of improved PRRSV vaccines would benefit from an increased understanding of epitopes relevant to protection, including those recognized by antibodies which possess the ability to neutralize distantly related strains. In this work, a reverse vaccinology approach was taken; starting first with pigs known to have a broadly neutralizing antibody response and then investigating the responsible B cells/antibodies through the isolation of PRRSV neutralizing monoclonal antibodies (mAbs). PBMCs were harvested from pigs sequentially exposed to a modified-live PRRSV-2 vaccine as well as divergent PRRSV-2 field isolates. Memory B cells were immortalized and a total of 5 PRRSV-specific B-cell populations were isolated. All identified PRRSV-specific antibodies were found to be broadly binding to all PRRSV-2 isolates tested, but not PRRSV-1 isolates. Antibodies against GP5 protein, commonly thought to possess a dominant PRRSV neutralizing epitope, were found to be highly abundant, as four out of five B cells populations were GP5 specific. One of the GP5-specific mAbs was shown to be neutralizing but this was only observed against homologous and not heterologous PRRSV strains. Further investigation of these antibodies, and others, may lead to the elucidation of conserved neutralizing epitopes that can be exploited for improved vaccine design and lays the groundwork for the study of broadly neutralizing antibodies against other porcine pathogens.